2017
DOI: 10.1021/acs.jpclett.7b00593
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Bis(fluorosulfonyl)imide/Poly(ethylene oxide) Polymer Electrolyte for All Solid-State Li–S Cell

Abstract: Solid polymer electrolytes (SPEs) comprising lithium bis(fluorosulfonyl)imide (Li[N(SOF)], LiFSI) and poly(ethylene oxide) (PEO) have been studied as electrolyte material and binder for the Li-S polymer cell. The LiFSI-based Li-S all solid polymer cell can deliver high specific discharge capacity of 800 mAh g (i.e., 320 mAh g), high areal capacity of 0.5 mAh cm, and relatively good rate capability. The cycling performances of Li-S polymer cell with LiFSI are significantly improved compared with those with conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
163
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(175 citation statements)
references
References 32 publications
11
163
1
Order By: Relevance
“…The novel PCPI − and Huckel-type anions showed ionic conductivities on the order of 0.1 mS cm −1 above 50 and is higher than PEO 16 NaPF 6 based system. At 70 °C, PEO 16 NaTCP showed ionic conductivity values (so-called liquid-like) greater Judez et al [45] reported the preparation of polymer electrolyte based on lithium bis(fluorosulfonyl)imide Thiam et al [47] prepared the solvent-free and oligomer-free 3D polymer electrolytes. The DSC analysis shows the decrease of T m and ∆H m after cross-linking and it may be due to the constraint produced by the cross-linking which reduces the tendency of the chain re-organization.…”
Section: Polymer In Salt Systemmentioning
confidence: 99%
“…The novel PCPI − and Huckel-type anions showed ionic conductivities on the order of 0.1 mS cm −1 above 50 and is higher than PEO 16 NaPF 6 based system. At 70 °C, PEO 16 NaTCP showed ionic conductivity values (so-called liquid-like) greater Judez et al [45] reported the preparation of polymer electrolyte based on lithium bis(fluorosulfonyl)imide Thiam et al [47] prepared the solvent-free and oligomer-free 3D polymer electrolytes. The DSC analysis shows the decrease of T m and ∆H m after cross-linking and it may be due to the constraint produced by the cross-linking which reduces the tendency of the chain re-organization.…”
Section: Polymer In Salt Systemmentioning
confidence: 99%
“…On the other hand, the stability and compatibility with the metal lithium anode interface is among the most urgent challenges to be addressed in order to ensure long‐term stability . For example, in the ASSLSBs using the widely used PEO‐lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) SPE, the solid electrolyte interphase (SEI) layer formed on the lithium anode suffers from inferior quality, which directly lead to lithium polysulfide shuttling even in the earliest charge/discharge cycling . Therefore, it is important to stabilize the lithium anode interface and keep lithium polysulfides from shuttling in the SPE.…”
Section: Introductionmentioning
confidence: 99%
“…The developed polymer-based SSEs demonstrated high ionic conductivity and good accommodation with Li metal anode which breaks the bottleneck that allow the polymer-based ASS Li-S batteries operating at ambient temperature. Many groups have attempted to develop hybrid electrolytes with the combination of polymer and oxide-based electrolytes, which demonstrated enhanced stability and conductivity [411][412][413][414][415]. Despite the excellent electrochemical performance, the loading of these sulfur and Li 2 S-based cathodes are unsatisfactory and unsuitable for commercial application.…”
Section: Polymer Electrolyte-based Li-s Batteriesmentioning
confidence: 99%